Selectivity of the NF-κB Response - Sen, Ranjan (Cold Spring Harbor Laboratory Press, 2010)
NF-κB is activated by many stimuli and NF-κB binding sites have been identified in a wide variety of genes. Yet, NF-κB-dependent gene expression must be stimulus- and cell-type-specific. In others words, the cellular response to different NF-κB activating stimuli, such as TNFα, IL-1, and LPS, must be different; and the response of different cell types, such as lymphocytes, fibroblasts, or epithelial cells, to the same NF-κB-inducing stimulus must also be different. Finally, kinetics of gene expression must be accounted for, so that all NF-κB-dependent genes are not activated simultaneously even if cell type and stimulus are constant. Here, we explore the mechanistic framework in which such regulatory aspects of NF-κB-dependent gene expression have been analyzed because they are likely to form the basis for physiological responses.